2019
DOI: 10.3390/molecules24152753
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Perspectives of Molecules from Urtica dioica Extracts for Cancer Treatment

Abstract: A large range of chronic and degenerative diseases can be prevented through the use of food products and food bioactives. This study reports the health benefits and biological activities of the Urtica dioica (U. dioica) edible plant, with particular focus on its cancer chemopreventive potential. Numerous studies have attempted to investigate the most efficient anti-cancer therapy with few side effects and high toxicity on cancer cells to overcome the chemoresistance of cancer cells and the adverse effects of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 140 publications
(160 reference statements)
1
32
0
2
Order By: Relevance
“…Despite all these studied effects of UD extracts, data showing clinical evidence for its anti-cancer effect are scarce and limited to a few in vitro studies on breast, prostate, and, recently, lung cancer cell lines, in addition to some animal models, that involved different formulations of UD leaf extract [ 17 , 18 ]. For instance, a study conducted by Mohammadi et al showed that the dichloromethane extract of UD leaves inhibited the growth and proliferation of human prostate cancer cells (PC3), with an IC 50 concentration of 15.54 µg/mL after 48 h of treatment [ 19 ]. In addition, recent studies have focused on its synergistic effect on cancer cell lines when combined with standard chemotherapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these studied effects of UD extracts, data showing clinical evidence for its anti-cancer effect are scarce and limited to a few in vitro studies on breast, prostate, and, recently, lung cancer cell lines, in addition to some animal models, that involved different formulations of UD leaf extract [ 17 , 18 ]. For instance, a study conducted by Mohammadi et al showed that the dichloromethane extract of UD leaves inhibited the growth and proliferation of human prostate cancer cells (PC3), with an IC 50 concentration of 15.54 µg/mL after 48 h of treatment [ 19 ]. In addition, recent studies have focused on its synergistic effect on cancer cell lines when combined with standard chemotherapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tłoczenie jest odpowiednią metodą pozyskiwania oleju z roślin oleistych o dużej zawartości kwasów tłuszczowych, jednak nie jest efektywne w przypadku roślin z mniejszą ich zawartością. Z tego względu w niniejszej pracy zastosowano ekstrakcję za pomocą dwutlenku węgla w stanie nadkrytycznym do pozyskania kwasów tłuszczowych z liści pokrzywy zwyczajnej o znanych właściwościach prozdrowotnych [2,4,6].…”
Section: Wprowadzenieunclassified
“…Recent meta-analyses showed that the effectiveness of Serenoa repens is similar or slightly inferior compared to finasteride and tamsulosin, but clearly higher than the placebo in the treatment of mild and moderate low urinary tract symptoms (LUTS), nocturia, and discomfort [21]. The combination with Urtica dioica has been proposed according to its anti-inflammatory and antioxidant activities [22,23]. In particular, we investigated whether the combination of Urtica dioica and Serenoa repens extracts permits the reduction of inflammation and oxidative stress in an in vitro cell model of prostatic hyperplasia (BPH-1 cell line).…”
Section: Introductionmentioning
confidence: 99%